Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1440-1754.2011.02059.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and academic performance in Indigenous Australian children from a remote community: An exploratory study

Abstract: Aim:  Disruptions to sleep in childhood are associated with poor behaviour and deficits in academic performance and executive function. Although academic performance of indigenous children from remote communities in Australia is documented as well below that of non‐indigenous children, the extent of sleep disruption and its contribution to academic performance among this population has not been assessed. This pilot study aimed to objectively assess the sleep of remote indigenous children and the association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…To date, only four small studies have assessed sleep and sleep related issues in the paediatric ATSI population. 8,9,10,11 Therefore, we reviewed the prevalence of OSA in the paediatric ATSI group and the impact of a paediatric sleep service in the NT.…”
Section: Darwin Respiratory and Sleep Health Clinic Darwin Northernmentioning
confidence: 99%
“…To date, only four small studies have assessed sleep and sleep related issues in the paediatric ATSI population. 8,9,10,11 Therefore, we reviewed the prevalence of OSA in the paediatric ATSI group and the impact of a paediatric sleep service in the NT.…”
Section: Darwin Respiratory and Sleep Health Clinic Darwin Northernmentioning
confidence: 99%
“…Recent findings on the sleep of Indigenous children suggest that this group may also be encumbered with a higher prevalence of sleep problems 3 . ‐ 7 …”
mentioning
confidence: 99%
“…1 A recent Australian community cohort study reported an OSA (AHI ≥ 10) prevalence of 53% in males age 40 y or older, and a moderate (AHI [20][21][22][23][24][25][26][27][28][29] to severe (AHI ≥ 30) OSA prevalence of 26%. 7 Comparable studies of indigenous peoples from New Zealand 8 and Canada 9 reported a Māori OSA prevalence of 14% (RDI ≥ 5), 11% (RDI ≥ 10) and 6% (RDI ≥ 15), and American Indian OSA prevalence of 33% (AHI [5][6][7][8][9][10][11][12][13][14] and 23% (AHI ≥ 15).…”
mentioning
confidence: 99%
“…Cooper et al's similarly small study of 21 Indigenous children age 6-13 y in northern Australia suggested that increasing age was significantly associated with greater sleep latency and reduced sleep efficacy, and that movement during sleep and sleep fragmentation was associated with reduced academic performance. 12 The third and larger study by Valery et al investigated the prevalence of snoring and restlessness and its relationship with asthma in 1,650 Indigenous children in five communities in the Torres Strait region. 13 The prevalence of restless sleep was 6% and snoring 14.2% and both were associated with a coexistent diagnosis of asthma.…”
mentioning
confidence: 99%
See 1 more Smart Citation